The Effect of Slightly Upward and Downward Inclined Pipes on the Stability of Gas-Oil Two-Phase Flow - Peyman Sabzi; Saheb Noroozi (ASEAN Journal of Chemical Engineering, 2014)
Pipeline inclination has an important effect on the stability of two-phase flow and flow assurance in the pipeline. This inclination may be intentional; it may be inevitable in pipeline installation; or it may be due to an error in pipeline installation. In this situation, even the slight inclination of the pipe plays an important role in the growth or elimination of the instability of the two-phase flow. In this study using a code designed for the analysis of pipelines’ two-phase flow, the stability of the two-phase flow for Kerosene oil flow along with methane gas has been compared in downward inclined pipes, upward inclined pipes, and horizontal pipes. Using the mentioned computer code, it has been proved that the pipe’s upward inclination results in the increase of two-phase flow instability, while the pipe’s downward inclination is helpful in two-phase flow stability. In order to model two-phase flow in the pipe, two-fluid model has been used. This model considers each phase separately and the equations of mass conservation and momentum are written for each phase. The momentum exchange between the two phases and between each phase and the pipe wall has been considered. Conservation equations have been solved using SIMPLE algorithm in a numerical form with finite volume method.Keywords: Pipes, Two-Phase Flow, Inclined Stability, Two-Fluid Model